2019
DOI: 10.3390/nu11061258
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Adenosine Receptors and Antioxidative Effect of Beer Extracts in in Vitro Models

Abstract: The fight against neurodegenerative diseases is promoting the searching of nutrients, preferably of wide consumption, with proven effects on health. Beer is widely consumed and has potential benefits on health. In this work, three different extracts from dark beer (DB), non-alcoholic beer (NAB), and lager beer (LB) were assayed at 30 min and 24 h in rat C6 glioma and human SH-SY5Y neuroblastoma cells in order to study their possible protective effects. Cell viability and adenosine A1, A2A, A2B, and A3 receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 85 publications
2
8
0
Order By: Relevance
“…Chromatographic analysis was performed with Ultimate 3000U-HPLC, and data peaks were processed with Chromeleon 7 (ThermoFisher, Madrid, Spain) as previously described ( Alonso-Andres et al, 2019 ). An HPLC diode array was used working at 254 nm wavelength.…”
Section: Methodsmentioning
confidence: 99%
“…Chromatographic analysis was performed with Ultimate 3000U-HPLC, and data peaks were processed with Chromeleon 7 (ThermoFisher, Madrid, Spain) as previously described ( Alonso-Andres et al, 2019 ). An HPLC diode array was used working at 254 nm wavelength.…”
Section: Methodsmentioning
confidence: 99%
“…Previous results of our group have demonstrated that beer extracts (lager, nonalcoholic, and dark beer) modulate adenosine receptors and protect from oxidative stress in cell cultures . We do not know which compounds are responsible for these effects, but we can point to common ingredients like hops.…”
Section: Introductionmentioning
confidence: 92%
“…45 In fact, both adenosine A 1 and A 2A receptor levels are increased after treatment with NH or CH, and this increase is similar to that which we reported previously when using beer extracts. 45 Interestingly, Nugget and Columbus hops are frequently used during brewing and could be responsible for the increase elicited by different beer extracts.…”
Section: Effect Of Xanthohumol In C6 and Sh-sy5y Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, in this case, ethanol was not tested. Similarly, a total extract obtained from dark beer conferred higher protection to rat C6 glioma and human SH-SY5Y neuroblastoma cells against an oxidant stressor challenge (hydrogen peroxide) compared total extracts obtained from non-alcoholic and lager beers [ 91 ]. Again, neither the phenolic compounds of beers nor an alcoholic reconstituted extract were tested.…”
Section: Phenols-related Health Effects Of Beer Consumptionmentioning
confidence: 99%